2020
DOI: 10.1016/j.autcon.2020.103129
|View full text |Cite
|
Sign up to set email alerts
|

Automatic generation of building information models from digitized plans

Abstract: This paper proposes a new approach to creating Building Information (BIM) models of existing buildings from digitized images. This automatic approach is based on three main steps. The first involves extracting the useful information automatically from rasterized plans by using image processing techniques that include segmentation, filtering, dilation, erosion, and contour detection. This information feeds the knowledge base of an expert system for BIM model generation. In the second step, using the knowledge b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
0
12
0
5
Order By: Relevance
“…3.3 Core features of the fourth generation urban design paradigm: transformation of technical methods and tools Digitalization is to convert many complex and variable information into numbers and data that can be measured, and then use these numbers and data to establish an appropriate digital model, transform them into a series of binary codes, and introduce them into the internal computer for unified processing, which is the basic process of digitization [17][18][19]. Digitalization focuses on results and organizes digitized information in an orderly way, which is convenient for enquiry retrieval, intelligent analysis and provision of solutions to relevant decisionmaking problems.…”
Section: Paradigm Of the Fourth Generation Urban Design: Human-computer Interactionmentioning
confidence: 99%
“…3.3 Core features of the fourth generation urban design paradigm: transformation of technical methods and tools Digitalization is to convert many complex and variable information into numbers and data that can be measured, and then use these numbers and data to establish an appropriate digital model, transform them into a series of binary codes, and introduce them into the internal computer for unified processing, which is the basic process of digitization [17][18][19]. Digitalization focuses on results and organizes digitized information in an orderly way, which is convenient for enquiry retrieval, intelligent analysis and provision of solutions to relevant decisionmaking problems.…”
Section: Paradigm Of the Fourth Generation Urban Design: Human-computer Interactionmentioning
confidence: 99%
“…Doukari e Greenwood [2] apresentaram um método para geração automática de modelos de informações de construção a partir da digitalização de imagens do Google Earth e desenvolvimento de modelos baseados em identificação de massa. Esse método se fundamenta em leitura de imagem, conversão da escala de cores Red, Green, Blue (RBG) para a escala de tons de cinza, em seguida aplicação computacional do filtro Gaussiano para melhorar a qualidade da imagem obtida, recorrendo juntamente a ferramenta Canny filter [13] que aprimora os contornos para em seguida aplicar o Canny Edge Detection, podendo dessa forma detectar fragmentos da imagem e reconhecer elementos para extração, avaliação e seleção desses contornos sendo o objetivo final dessa metodologia usada como base estimar a densidade habitacional a partir de imagens de satélites, por exemplo, que não se aplica no que se almeja obter nessa pesquisa [2].…”
Section: Metodologiaunclassified
“…Assim, nossa metodologia trata de adaptar a metodologia proposta por Doukari e Greenwood [2], mas com um objetivo final diferente. O objetivo desta pesquisa é usar a leitura de imagem a partir de documentos 2D para a partir destes desenvolver o modelo das edificações e armazenar os dados em extensão IFC (Industry Foundation Classes) produzido pela linguagem de programação e compatível com os programas de tecnologia BIM.…”
Section: Metodologiaunclassified
See 1 more Smart Citation
“…Zhu et al [16] identified and tracked the workforce and equipment from construction jobsite videos. Doukari and Greenwood [17] automatically extracted useful information from rasterized plans using image processing techniques.…”
Section: Introductionmentioning
confidence: 99%